Imposition of MAT on SEZs: Concerns and the way forward - Arpita Mukherjee; Bhavook Bhardwaj (Indian Council for Research on International Economic Relations (ICRIER), 2016)
A Special Economic Zone (SEZ) is a type of managed industrial cluster which focuses on exports and encourages the inflow of foreign direct investment (FDI) and technology. These "special" zones are given a range of fiscal and non-fiscal incentives, which are not available to firms located in the rest of the country. Fiscal incentives largely include tax concessions. While there can be arguments for or against giving fiscal incentives to an industrial cluster, in practice, a number of developing countries, which promote SEZs, provide tax incentives. Some of these incentives are actionable or even prohibited under the World Trade Organization's (WTO) Subsidies and Countervailing Measures Agreement. Given this background, this paper focuses on one such direct tax incentive, namely, the exemption from minimum alternate tax (MAT), and the implication of its withdrawal on Indian SEZ developers and units. Based on secondary data, the paper tries to examine if the withdrawal of the MAT exemption from 1 April, 2012, has adversely affected the performance of Indian SEZs. Based on a primary survey, it tries to understand the importance of direct tax benefits, including MAT exemption, for SEZ developers and units. The paper also examines the direct tax incentives given to SEZs across countries such as Bangladesh, Philippines, Republic of Korea, United Arab Emirates (Dubai) and Vietnam, with whom India competes to get FDI and technology. The paper concludes that all countries provide direct tax incentives to SEZs, and hence, if India wants to continue with the SEZ policy, it has to provide the direct tax incentives. However, such incentives are not unconditional and have to be phased out over time. The paper identifies the gaps in the design of direct tax incentives, focusing on the income tax and MAT exemptions. It makes policy recommendations on how to make the SEZ policy successful and an instrument of the "Make in India" Campaign.
Keywords: E24; E25; J21; J31; L60; O33; 330; SEZs; fiscal policy; India; income tax; minimum alternate tax (MAT); trade policy